SECOND LANGUAGE LEARNERS’ ATTITUDES AND STRATEGIES IN LEARNING ENGLISH AS A FOREIGN LANGUAGE - Istiyani, Eva (Universitas Muhammadiyah Surakarta, 2014)
This study focused on comparison of learner?s attitude and strategies in learning En- glish between the high and low achievers. The qualitative descriptive analytic method is implemented in this study. The 10 ninth graders of MTs Darul Ulum Bandungharjo were chosen as the subject of the study and questionnaires are used as the research instru- ment. The study found that the high and low achievement students had positive atti- tudes towards community, people who speak English, and English in general. However, there was differences between high and low achiever?s attitudes towards English. The high-achievement students argued that they prefered English than other subjects. On the other hand, the low-achievement students disagreed with the statement. This condi- tion showed that attitude was personal. Morever, the strategies were differ from the high and low achievement student. The study found that the high-achievement students used cognitive and metacognitive strategies to improve their ability in English. How- ever, the low-achievement students used only some of cognitive strategies in learning English. As a summary, cognitive and metacognitive strategies accompanied by posi- tive attitude and motivation influenced the learners? achievements of English skills.